2020
DOI: 10.1021/acs.chemmater.0c00781
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Size-Focused Growth of Indium Phosphide Nanocrystals in the Presence of Trace Water

Abstract: Indium phosphide (InP) nanocrystals have emerged as a viable alternative to heavy metal-based colloidal quantum dots for optoelectronic applications. Traditionally, the presence of trace amounts of water during the synthesis of colloidal quantum dots is considered an undesired impurity because it prevents or slows down colloidal growth and alters the surface properties. Here, we report that fine-tuning the amount of trace water is the key for achieving sizefocused growth of monodisperse InP nanocrystals synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…38,39 Finally, a recent study has shown that trace water improves the size distribution obtained from InX 3 /P(NR 2 ) 3 , a variable not explored in our work. 40 The kinetics of InP formation is monitored by measuring the optical absorption (λ = 413 nm) of timed aliquots. 27 Although large cluster intermediates (>[InP] 20 ) could, in principle, contribute to the absorption at this wavelength, no spectroscopic signatures of clusters were observed herein nor has any evidence for InP clusters been reported for syntheses conducted with InX 3 /P(NR 2 ) 3 .…”
Section: S3mentioning
confidence: 99%
“…38,39 Finally, a recent study has shown that trace water improves the size distribution obtained from InX 3 /P(NR 2 ) 3 , a variable not explored in our work. 40 The kinetics of InP formation is monitored by measuring the optical absorption (λ = 413 nm) of timed aliquots. 27 Although large cluster intermediates (>[InP] 20 ) could, in principle, contribute to the absorption at this wavelength, no spectroscopic signatures of clusters were observed herein nor has any evidence for InP clusters been reported for syntheses conducted with InX 3 /P(NR 2 ) 3 .…”
Section: S3mentioning
confidence: 99%
“…On the other hand, colloidal semiconductor nanocrystals (NCs) have been exploited in academic and industrial sectors for more than 30 years, mainly via trial-and-error basis synthetic development owing to their unresolved reaction kinetics and thermodynamics 3 11 . Due to the co-existence of metastable states with similar energy, unraveling the reaction pathways in full detail has been difficult 12 16 .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] To date, considerable research has focused on growth kinetics and synthetic strategies of InP QDs. [19][20][21][22][23][24][25] Apart from the common method where indium acetate and tris(trimethylsilyl)phosphine ((TMS) 3 P) are utilized, indium halide is widely employed in the preparation of InP/ ZnS QDs combining with zinc halide and amino phosphine recently owing to its low cost and safety. As has been reported, halide plays a critical role in its nucleation and surface chemistry.…”
mentioning
confidence: 99%